Invasive histiocytoma in the ear canal of a dog. Issue 4 (6th April 2020) - Fernandez, Monica; Boudreaux, Bonnie B.; Wilson, Leslie; Moore, Peter F.; Rademacher, Nathalie; Pucheu‐Haston, Cherie
Abstract : Background: Cutaneous histiocytomas (CH) are derived from epidermal Langerhans cells. Single CH are generally associated with a good prognosis in dogs because most undergo spontaneous remission. However, aggressive behaviour and lymph node metastasis have been reported in a small number of dogs with single CH. Objective: To describe the clinical presentation, treatment and disease progression of an aggressive CH located in the ear canal of a dog. Animal: An 8‐year‐old intact male Rottweiler dog. Methods and materials: A unilateral ear canal mass was identified as a CH on routine haematoxylin and eosin stained samples. The diagnosis was confirmed by the demonstration of markers associated with Langerhans cells (Iba‐1, E‐cadherin and CD18) and the absence of markers associated with B cells (CD79a, CD20, Pax5), T cells (CD3), plasma cells (Mum‐1) and macrophages (CD11d, CD204). Results: A total ear canal ablation was performed, but tumour cells extended throughout the horizontal canal and to the deep surgical margin. Due to the locally invasive nature of the mass and incomplete excision, adjunctive chemotherapy with CCNU was pursued. No measurable local disease was appreciable at the time of the last treatment. At 250 days post‐surgery the dog was euthanized owing to the development of multiple abdominal masses. No evidence of local tumour recurrence was noted. Conclusions and clinical importance: Although single CH are typically associated with benign behaviour, the mass in this dog demonstrated locally invasive behaviour. Cutaneous histiocytomas in the ear canals of dogs may represent a particularly aggressive variant of the condition. Abstract : Background – Cutaneous histiocytomas (CH) are derived from epidermal Langerhans cells. Single CH are generally associated with a good prognosis in dogs because most undergo spontaneous remission. However, aggressive behaviour and lymph node metastasis have been reported in a small number of dogs with single CH. Objective – To describe the clinical presentation, treatment and disease progression of an aggressive CH located in the ear canal of a dog. Conclusions and clinical importance – Although single CH are typically associated with benign behaviour, the mass in this dog demonstrated locally invasive behaviour. Cutaneous histiocytomas in the ear canals of dogs may represent a particularly aggressive variant of the condition. Résumé: Contexte: Les histiocytomes cutanés (CH) sont issus des cellules de Langerhans épidermiques. Un CH unique est généralement de bon pronostic chez le chien, la majorité rétrocédant spontanément. Cependant, une évolution agressive et des métastases ganglionnaires ont été décrites dans un faible nombre de cas de CH unique. Objectif: Décrire la présentation clinique, le traitement et l'évolution d'un CH agressif localisé dans le conduit auriculaire d'un chien. Sujet: Un Rottweiler mâle entier de 8 ans. Matériels et méthodes: Une masse unilatérale du conduit auriculaire a été identifié comme un CH par examen histopathologique coloré à l'hémalun‐éosine. Le diagnostic a été confirmé par la disposition de marqueurs associés à des cellules de Langerhans (Iba‐1, E‐cadhérine et CD18) et l'absence de marqueurs associés aux cellules B (CD79a, CD20, Pax5), cellules T (CD3), cellules plasmatiques (Mum‐1) et macrophages (CD11d, CD204). Résultats: Une ablation totale du conduit auriculaire a été réalisée mais les cellules tumorales s'étendaient au delà de la paroi horizontale et aux marges chirurgicales profondes. En raison de la nature localement invasive et de l'exérèse incomplète, une chimiothérapie d'appoint avec CCNU a été instaurée. Aucune lésion mesurable n'était observée lors du dernier traitement. A 250 jours après la chirurgie le chien a été euthanasié en raison du développement de masses abdominales multiples. Aucune preuve de récidive tumorale locale n'a été notée. Conclusions et importance clinique: Bien qu'un CH unique soit typiquement associé à une évolution bénigne, la masse chez ce chien a montré un comportement invasif local. Les histiocytomes cutanés du conduit auriculaire du chien pourraient représenter une variante particulièrement agressive. Resumen: Introducción: los histiocitomas cutáneos (CH) se derivan de las células epidérmicas de Langerhans. Los CH únicos generalmente se asocian con un buen pronóstico en los perros porque la mayoría experimenta una remisión espontánea. Sin embargo, se ha reportado un comportamiento agresivo y metástasis en ganglios linfáticos en un pequeño número de perros con CH único. Objetivo: describir la presentación clínica, el tratamiento y la progresión de la enfermedad de un CH agresivo ubicado en el canal auditivo de un perro. Animal: un perro Rottweiler macho entero de 8 años. Métodos y materiales: se identificó una masa unilateral del canal auditivo como CH en muestras teñidas con hematoxilina y eosina de rutina. El diagnóstico fue confirmado por la demostración de marcadores asociados con las células de Langerhans (Iba‐1, E‐cadherina y CD18) y la ausencia de marcadores asociados con las células B (CD79a, CD20, Pax5), células T (CD3), células plasmáticas (MUM ‐ 1) y macrófagos (CD11d, CD204). Resultados: se realizó una ablación total del canal auditivo, pero las células tumorales se extendieron por todo el canal horizontal y hasta el margen quirúrgico profundo. Debido a la naturaleza localmente invasiva de la masa y la escisión incompleta, se utilizó quimioterapia adyuvante con CCNU. Ninguna enfermedad local visible fue apreciable en el momento del último tratamiento. A los 250 días después de la cirugía, el perro fue sacrificado debido al desarrollo de múltiples masas abdominales. No se observó evidencia de recurrencia tumoral local. Conclusión e importancia clínica: aunque el CH solitario se asocia típicamente con un comportamiento benigno, la masa en este perro demostró un comportamiento localmente invasivo. Los histiocitomas cutáneos en los canales auditivos de los perros pueden representar una variante particularmente agresiva de la afección. Zusammenfassung: Hintergrund: Kutane Histiozytome (CH) entspringen den epidermalen Langerhans Zellen. Einzelne CH werden generell mit einer guten Prognose bei Hunden gesehen, weil die meisten eine spontane Remission durchlaufen. Es wurde jedoch auch aggressives Wachstum und Lymphknotenmetastasierung in einer geringen Anzahl von Hunden mit einzelnen CH beschrieben. Ziel: Eine Beschreibung der klinischen Präsentation, der Behandlung und des Krankheitsfortschritts bei einem aggressiven CH, welcher im Ohrkanal eines Hundes wuchs. Tiere: Es handelt sich um einen 8‐jährigen intakten Rottweilerrüden. Methoden und Materialien: Es wurde eine unilaterale Masse im Ohr mittels routinemäßiger Hämatoxylin und Eosin Färbung als CH beschrieben. Die Diagnose wurde durch den Nachweis von Langerhans Zell Markern (Iba‐1, E‐Cadherin und CD 18), sowie einer Abwesenheit von B‐Zell Markern (CD79a, CD20, Pax5), T Zellen (CD3), Plasmazellen (Mum‐1) und Makrophagen (CD11d, CD204) bestätigt. Ergebnisse: Es wurde eine Totale Ohrkanalablation durchgeführt, aber die Tumorzellen erstreckten sich entlang des gesamten Horizontalkanals und in die Tiefe der chirurgischen Exzisionslinie. Aufgrund der lokal invasiven Natur der Masse und der unvollständigen Entfernung wurde eine zusätzliche Chemotherapie mit CCNU durchgeführt. Zum Zeitpunkt der letzten Behandlung konnte lokal keine krankhafte Veränderung mehr festgestellt werden. Zweihundertfünfzig Tage nach der Operation wurde der Hund aufgrund der Entwicklung multipler abdominaler Massen eingeschläfert. Es wurde zu diesem Zeitpunkt kein lokales Wiederwachsen des Tumors festgestellt. 要約: 背景: 皮膚組織球腫(CH)は表皮ランゲルハンス細胞に由来する。孤立性CHは、ほとんどが自然寛解を経験するため、一般的に犬の良好な予後と関連している。しかしながら、孤立性CHに罹患した少数の犬で悪性挙動およびリンパ節転移が報告されている。 目的: 本研究における目的は、ある犬の外耳道に発生した悪性挙動CHの臨床症状、治療、および疾患の進行を説明することであった。 供試動物: 8歳、雄のロットワイラー。 材料と方法: 通常のヘマトキシリンおよびエオジン染色サンプルにより片側外耳道腫瘍をCHと特定した。診断は、ランゲルハンス細胞(Iba‐1、E‐カドヘリン、CD18)関連マーカーの実証およびB細胞(CD79a、CD20、Pax5)、T細胞(CD3)、形質細胞( Mum‐1)およびマクロファージ(CD11d、CD204)関連マーカーの欠如によって確認した。 結果: 全耳道切除術を実施したが、腫瘍細胞は水平耳道全体および深部手術縁まで広がっていた。腫瘤の局所侵襲性および不完全切除のため、CCNUによる補助化学療法を実施した。最終治療点では、測定可能な局所疾患は認められなかった。犬は手術後250日で、複数の腹部腫瘤が発生したため、安楽死させられた。局所腫瘍再発の証拠は認められなかった。 結論と臨床的重要性: 通常、孤立性CHは良性挙動に関連付けられているが、供試犬の腫瘍は局所的に侵襲的な挙動を示した。犬の外耳道の皮膚組織球腫は、この疾患において特に攻撃的な変異型である可能性がある。 摘要: 背景: 皮肤组织细胞瘤 (CH) 来源于表皮郎格罕细胞。因为犬的单个CH大多数能自愈, 所以通常预后良好。然而, 在少数单个 CH患犬的病例报告中, 发现了侵袭行为和淋巴结转移。 目的: 描述位于犬耳道的侵袭性CH的临床表现、治疗和发病过程。 动物: 8 岁、未去势雄性罗威纳犬。 方法和材料: 在常规苏木精和伊红染色样本中, 单侧耳道肿块被确定为 CH。通过证明郎格罕细胞标记物(Iba‐1、E‐cadherin 和 CD18)以及缺乏 B 细胞 (CD79a、CD20、Pax5)、T 细胞 (CD3)、浆细胞 (Mum‐1) 和巨噬细胞 (CD11d、CD204) 标记物来确诊。 结果: 进行全耳道切除, 但肿瘤细胞延伸至整个水平耳道和深部手术边缘。由于肿块局部侵袭性强, 切除不彻底, 给予CCNU 作为辅助化疗。末次治疗时未检测到局部疾病。术后 250 天, 由于出现多个腹部肿块, 对犬实施安乐死。未观察到局部肿瘤复发证据。 结论和临床重要性: 尽管单个CH的生物学行为通常为良性, 但该犬的肿块表现出局部侵袭行为。犬耳道中的皮肤组织细胞瘤可能代表了该疾病一种特殊的具有侵袭性的变体。 Resumo: Contexto: Os histiocitomas cutâneos (HC) são derivados de células de Langerhan epidérmicas. O HC único está geralmente associado a um bom prognóstico em cães, porque a maioria sofre remissão espontânea. No entanto, comportamento agressivo e metástase para linfonodos foram relatados em um pequeno número de cães com HC único. Objetivos: Descrever a apresentação clínica, o tratamento e a progressão da doença de um HC agressivo localizado no conduto auditivo de um cão. Animal: Um cão Rottweiler macho intacto de 8 anos de idade. Métodos e materiais: Uma massa unilateral no conduto auditivo foi classificada como HC nas amostras coradas com hematoxilina e eosina. O diagnóstico foi confirmado pela demonstração de marcadores associados às células de Langerhans (Iba ‐ 1, E ‐ caderina e CD18) e pela ausência de marcadores associados às células B (CD79a, CD20, Pax5), células T (CD3), plasmócitos (Mum‐1) e macrófagos (CD11d, CD204). Resultados: Realizou‐se ablação total do canal auditivo, mas as células tumorais se estenderam por todo o conduto horizontal e até a margem cirúrgica profunda. Devido à natureza localmente invasiva da massa e excisão incompleta, foi realizada quimioterapia adjuvante com CCNU. Nenhuma doença local mensurável foi observada no momento do último tratamento. Aos 250 dias após a cirurgia, o cão foi eutanasiado devido ao desenvolvimento de várias massas abdominais. Nenhuma evidência de recorrência local do tumor foi observada. Conclusão e importância clínica: Embora um único HC esteja tipicamente associado a um comportamento benigno, a massa neste cão demonstrou um comportamento localmente invasivo. Histiocitomas cutâneos nos condutos auditivos de cães podem representar uma variante particularmente agressiva da doença.